A CONCEPTUAL PAPER ON NAZAFAH RUHIYYAH AND ITS EFFECT ON PURIFYING WEALTH THROUGH ZAKAH - Wan Mohd Firdaus Wan Mohamad,; Siti Maziah Ab Rahman,; Rikinorhakis Ridzwan, (Journal of Islamic, Social, Economics and Development, 2024)
One of the major tenets of Islamic teachings, zakah requires Muslims who can afford to give a portion of their wealth to those who merit it. There is an inner component to the outward act of paying zakah that has to do with a person's mindset and willingness to fulfil the duty. "Nazafah ruhiyyah" describes an individual's inner disposition or tendency to understand the true nature of belongings, acknowledge one's attachment to the material world, and be conscious of and compassionate towards others. The purpose of this study is to investigate the potential impact of zakah giving on the purification of property under Nazafah ruhiyyah. We used a qualitative analysis approach in this study and interviewed corporate representatives and Muslims in-depth. Thematic analysis is used to examine this qualitative data to find recurring themes and patterns in the participants' experiences. The study's findings demonstrate the importance of Nazafah Ruhiyyah in the experience of purifying property through zakah giving. A strong inner attitude helps them to let go of the sense of ownership and acknowledge the transient nature of material possessions, such as a sense of attachment to the property as a trust from God. Furthermore, Nazafah Ruhiyyah inspires people to be motivated to assist others by emulating the virtues of love, empathy, and compassion for the underprivileged community. The experience of Zakah also involves a significant component of social responsibility awareness. People with strong spiritual qualities believe that businesses and individuals have a duty to better society and lessen the suffering of others. This study sheds important light on the relationship between Nazafah Ruhiyyah and zakah's purification of wealth. Understanding this internal component helps us to recognise the spiritual principles that zakah embodies, which elevates it to the status of a kind of worship and an act of deference to God. It is anticipated that this study will add to the body of knowledge regarding zakah and serve as a foundation for future investigations into how best to comprehend and enhance the experience of purifying wealth through zakah within the framework of Muslim society.